ANALYSIS OF THE PROPERTIES OF NEW GROUPS OF COATINGS APPLIED IN HIGHLY LOADED MACHINE COMPONENTS - Kinga CHRONOWSKA; Marcin KOT; Łukasz MAJOR (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents an overview of new groups of tribological coatings with complex microstructure deposited by PVD (Physical Vapour Deposition) and CVD (Chemical Vapor Deposition) techniques. The results of microstructure studies (TEM), mechanical and tribological properties of nanocomposite coatings nc-Cr2C/a-C:H and multilayers 16x(Ti/TiN) were shown. The properties of these modern coatings are compared with the properties of two single coatings a-C:H and TiN. All coatings were deposited by magnetron sputtering on AISI 304 steel substrates. The hardness, elastic modulus and adhesion to the substrate studied by scratch testing were compared. The results showed the possibility of improving the wear resistance of the nanocomposite and multilayer coatings in comparison with conventional single coatings currently used in the machine industry.